Attenuated RORC Expression in the Presence of EMT Progression in Somatotroph Adenomas following Treatment with Somatostatin Analogs Is Associated with Poor Clinical Recovery - Lekva, Tove (Public Library of Science, 2013)
Somatostatin analogs (SA) have been established as the first line medical treatment for acromegaly, but following long-term treatment, SA normalizes GH and IGF-I levels in only 40–60% of patients. The epithelial marker E-cadherin plays a crucial role in the epithelial mesenchymal transition (EMT) and is associated with a poor response to SA treatment. We hypothesized that the characterization of transcripts regulated by SA in somatotroph adenomas with high and low E-cadherin expression may identify signaling pathways and mediators that can explain the poor response to SA treatment. We performed a microarray analysis of sixteen adenomas with different levels of E-cadherin and SA treatment to identify regulated transcripts. Candidate transcripts were further explored in vivo in sixty-five adenomas, and interactions between SA treatment and EMT progression on mRNA expression profiles and associations with clinical recovery were assessed. Finally, the effects of SA treatment on adenoma cells in vitro from acromegalic patients were determined. Microarray analysis of selected adenomas with differential E-cadherin expression, as a marker of EMT progression, identified 172 genes that displayed differential expression that was dependent on SA treatment. The validation of selected candidates in the entire cohort identified 9 transcripts that showed an interaction between E-cadherin expression and SA treatment. Further analysis of the impact of these genes suggests that attenuated RORC expression in somatotroph adenomas is associated with increased tumor size and a blunted clinical response. Our study indicates that attenuated RORC may be involved in the poor clinical response to SA treatment in patients with acromegaly.